2009
DOI: 10.1038/nsmb.1566
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional bases for broad-spectrum neutralization of avian and human influenza A viruses

Abstract: Influenza virus remains a constant public health threat, owing to its ability to evade immune surveillance through rapid genetic drift and reassortment. Monoclonal antibody (mAb)-based immunotherapy is a promising strategy for disease control. Here we use a human Ab phage display library and H5 hemagglutinin (HA) ectodomain to select ten neutralizing mAbs (nAbs) with a remarkably broad range among Group 1 influenza viruses, including the H5N1 “bird flu” and the H1N1 “Spanish flu” strains. Notably, nine of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
1,263
4
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,076 publications
(1,319 citation statements)
references
References 55 publications
37
1,263
4
4
Order By: Relevance
“…It has been reported that there exist highly conserved epitopes in the stem region of the HA molecule that may become a target for a "universal flu vaccine" (3,7,10,14,15). Humanized monoclonal antibodies raised against these conserved epitopes from a single influenza virus strain were shown to provide strong cross-protection against heterologous strains (13).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that there exist highly conserved epitopes in the stem region of the HA molecule that may become a target for a "universal flu vaccine" (3,7,10,14,15). Humanized monoclonal antibodies raised against these conserved epitopes from a single influenza virus strain were shown to provide strong cross-protection against heterologous strains (13).…”
Section: Discussionmentioning
confidence: 99%
“…The removal of glycosylation sites on the HA protein can expose conserved epitopes hidden by large glycans to elicit an immune response that recognizes HA variants at a higher titre . Broadly neutralizing HA2 stemspecific monoclonal antibodies with neutralizing activity for H1 clade viruses (Ekiert et al, 2009;Sui et al, 2009) and H3 subtype viruses (Bommakanti et al, 2010;Wang et al, 2010a) have been developed. These studies indicate that epitopes in the stem of HA are conserved and accessible to antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…These facts of conservation and sharing of the newly defined Replikins epitopes were not known, and this unawareness and the believed absence of conservation and sharing was the basis of the reason given for decades of not being able to make pan-influenza vaccines which could be used from year to year. However, having reviewed Replikins' technology since 2003 from data provided by the authors, the National Institutes of Health (NIH) first confirmed the influenza epitopes earlier defined by specific Replikins by landing anti-flu antibodies on them (16). This NIH data was simultaneously independently confirmed by studies at Scripps (17).…”
Section: Pan-influenza Vaccinesmentioning
confidence: 58%